Solid Phase Extraction of Ultra Trace Copper(II) Using Octadecyl Silica Membrane Disks Modified by Phendion Schiff Base - MOGHIMI, ALI (Asian Journal of Chemistry, 2010)
A simple and reproducible method for the rapid extraction and determination of trace amounts of copper(II) ions using octadecylbonded silica membrane disks modified by phendion. The method is based on complex formation on the surface of the ENVI-18 DISKTM disks followed by stripping of the retained species by minimum amounts of appropriate organic solvents. The elution is efficient and quantitative. The effect of potential interfering ions, pH, ligand amount, stripping solvent and sample flow rate were also investigated. Under the optimal experimental conditions, the break-through volume was found to about 1000 mL providing a preconcentration factor of 500. The maximum capacity of the disks was found to be 455 ± 5 μg for Cu2+. The limit of detection of the proposed method is 3 ng per 1000 mL. The method was applied to the extraction and recovery of copper in different water samples.